2014
DOI: 10.1155/2014/729827
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Swimming Exercise on Hippocampal Expression of Neurotrophic Factors in Rats Exposed to Chronic Unpredictable Mild Stress

Abstract: Depression is associated with stress-induced neural atrophy in limbic brain regions, whereas exercise has antidepressant effects as well as increasing hippocampal synaptic plasticity by strengthening neurogenesis, metabolism, and vascular function. A key mechanism mediating these broad benefits of exercise on the brain is induction of neurotrophic factors, which instruct downstream structural and functional changes. To systematically evaluate the potential neurotrophic factors that were involved in the antidep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 37 publications
4
47
1
1
Order By: Relevance
“…Increased GDNF mRNA expression in the hippocampus was also reported in a chronic unpredictable mild stress-induced depression model of rats [32]. However, a recent clinical investigation reported that the blood concentration of GDNF decreased in depressed patients [23], while antidepressant fluoxetine treatment in an animal model of Parkinson’s disease induced GDNF mRNA expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Increased GDNF mRNA expression in the hippocampus was also reported in a chronic unpredictable mild stress-induced depression model of rats [32]. However, a recent clinical investigation reported that the blood concentration of GDNF decreased in depressed patients [23], while antidepressant fluoxetine treatment in an animal model of Parkinson’s disease induced GDNF mRNA expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, enhanced level of caspase-3 (encoded by the CASP3 gene) -a proteolytic enzyme inducing cellular apoptosis -was observed in the cerebral cortex of rats, which experienced chronic mild stress (Bachis et al, 2008). Moreover, a prolonged exposure to stress results in a reduced expression of the antiapoptotic BCL-XL gene and enhanced expression of the proapoptotic BAX gene; whereas, reduced stress exposure promoted expression of the brain-derived neurotrophic factor (BDNF), nerve growth factor (VGF) and neuropeptide (NPY) genes in the hippocampus (Jiang et al, 2014).…”
Section: Molecular Genetic Studies Of Depressive Disordersmentioning
confidence: 99%
“…Different signaling pathways were reported to be involved in the upregulation of hippocampal neurogenesis, such as growth factor signaling (e.g. BDNF, VEGF) [63][64][65], short peptides (e.g. leptin, adiponectin) [66,67], and cell cycle regulation (e.g.…”
Section: Exercise and Adult Neurogenesis: Serotonin Signalingmentioning
confidence: 99%